Pengaruh Hedonistic Value, Utilitarian Value, dan Aesthetic Labor terhadap Behavioral Intention pada Konsumen KFC Indonesia - Muhammad Mirza Maulana; I Made Sukresna (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to analyze the effect of hedonistic value, utilitarian value, and aesthetic labor on behavioral intention with positive emotion as an intervening variable on KFC customers in Indonesia. According to data from KFC's financial statements, KFC experienced a decline in revenue growth from 2018 to 2020 and in the first three quarters of 2021 KFC's revenue fell from the previous period. The sample in this study amounted to 130 respondents, namely KFC customers in Indonesia. The sample collection method used is purposive sampling by distributing questionnaires to the respondents which are specifically addressed to KFC customers in Indonesia. In this study, a theoretical model was developed by proposing seven hypotheses to be tested using the Structural Equation Modeling (SEM) analysis tool operated through the AMOS 22 program. The results of this study indicate that hedonistic value affects behavioral intention directly but positive emotion cannot mediate between hedonistic values and behavioral intentions. On the other hand, utilitarian values and aesthetic labor do not have a direct influence on behavioral intention. However, when positive emotion acts as an intervening variable, it shows that there is a significant effect on behavioral intentions.